The use of microtechnology to monitor collision performance in professional rugby union - MacLeod, S. J.; Hagan, C.; Egaña, M.; Davis, J.; Drake, D. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine if microtechnology-derived collision loads discriminate between collision performance and compare the physical and analytical components of collision performance between positional groups. Methods: Thirty-seven professional male rugby union players participated in this study. Collision events from 11 competitive matches were coded using specific tackle and carry classifications based on the ball-carrier`s collision outcome. Collisions were automatically detected using 10 Hz microtechnology units. Collision events were identified, coded (as tackle or carry), and timestamped at the collision contact point using game analysis software. Attacking and defensive performances of 1609 collision events were analyzed. Results: Collision loads were significantly greater during dominant compared with neutral and passive collisions (P<?001; effect size [ES]=0.53 and 0.80, respectively), tackles (P<.0001; ES=0.60 and 0.56, respectively), and carries (P<.001; ES=0.48 and 0.79, respectively). Overall, forwards reported a greater number and frequency of collisions but lower loads per collision and velocities at collision point than did backs. Microtechnology devices can also accurately, sensitively, and specifically identify collision events (93.3%, 93.8%, and 92.8%, respectively). Conclusion: Microtechnology is a valid means of discriminating between tackle and carry performance. Thus, microtechnology-derived collision load data can be utilized to track and monitor collision events in training and games.